Broad-specificity ELISA with a heterogeneous strategy for sensitive detection of microcystins and nodularin. (February 2020) - Lu, Ning; Ling, Li; Guan, Tian; Wang, Lanteng; Wang, Dian; Zhou, Jiahui; Ruan, Ting; Shen, Xing; Li, Xiangmei; Sun, Yuanming; Lei, Hongtao
Abstract: A highly sensitive and broadly specific competitive indirect enzyme-linked immunosorbent assay (ciELISA) method was developed for the simultaneous detection of nine microcystins (MCs) and nodularin (NOD) using MC-LR-keyhole limpet hemocyanin (KLH) for New Zealand white rabbit immunization to produce antibodies. The MC-LR-bovine serum albumin (BSA) and NOD-BSA coating antigens were compared and heterogeneous coating strategy was found to significantly improve the sensitivity of detection, as evident from the appropriate structure. Comparison of the half-maximum inhibitory concentration (IC50) with MC-LR and MC-LR-BSA coating techniques (0.29 ng/mL) revealed the superior performance of 0.054 ng/mL for NOD-BSA coating. NOD-BSA was selected as the coating antigen, because it showed ultrahigh sensitivity for the detection of MC-LR with a limit of detection (LOD) of 0.0016 ng/mL, which was below the maximum residue level (MRL) of 1 ng/mL. In addition, high reproducibility, good stability, and acceptable spiked sample detection, as validated by liquid chromatography tandem mass spectrometry (LC-MS/MS), indicated the possible application of this method for the analysis of MCs and NOD in water sample. Highlights: An antibody recognizing 9 microcystins and nodularin was obtained for the first time. A heterogeneous coating strategy resulted to a high sensitivity. A highly sensitive and broadly specific competitive iELISA method was developed for the simultaneous detection of 9 microcystins and nodularin.